DIVERSITY AND DISTRIBUTION OF SOIL ARTHROPODS IN FOUR PLANT COMMUNITIES AT MT.TANGKUBAN PARAHU, WEST JAVA - , Shahabuddin
Abstract : A study on the the diversity and distribution of soil arthropods in four different plant communities, i.e. Pinus, Schima-Astronia, Vaccinium-Syzygium, and Vaccinium at Mt.Tangkuban Parahu ,West Java, was conducted from August 1997 to January 1998, using pitfall traps, quadrats and soil cores. Abiotic environmental factors at the sampling sites were also measured. Soil arthropods were separated from the litter and soil by hand sorting and floating methods. A total of 12908 soil arthropods belonging to 128 species of 94 families and 21 orders have been collected. The order of soil arthropods which species richness of 10 or more were Coleoptera (29 spp.), Araneae (20 spp.), Diptera (10 spp.), and Hymenoptera (10 spp.). Six species i.e. Lepidocyrtus sp., Salina sp., Folsomia sp., Paratrechynus sp., Pheidole plagiaria, and Lispinus sp., were found to be predominant in the four plant communities. Dicyrtomini sp. was the characteristic soil arthropods species in the Pinus community, Orchestia sp. in Schima-Astronia community, Catops sp. in Vaccinium-Syzygium community, and Paratemnus sp. and Pardosa sp in Vaccinium community. Result of the quadrat method showed two different major soil arthropods communities, namely the soil arthropods of the Vaccinium and those the remaining three plant communities. Species diversity and distribution of soil arthropods were correlated - spatially and temporally- with litter thickness, organic matter content, soil pH and air temperature. The abundance of each order of soil athropods, correlated with abiotic environmental factors with coefficient of correlation were varied. The species diversity index (H\') of soil arthropods in the four plant communities were discussed.